Production, Purification, and Characterization of α-Galactosidase from Monascus pilosus - Wong, Hin-Chung (1986)
A Monascus pilosus strain was selected for production of intracellular α-galactosidase. Optimum conditions for mycelial growth and enzyme induction were determined. Galactose was one of the best enzyme inducers. The enzyme was purified by ammonium sulfate precipitation, gel filtration, and ion exchange chromatography and was demonstrated to be homogeneous by slab gel electrophoresis. The molecular weight of this enzyme, estimated by gel filtration, was about 150,000. The optimum conditions for the enzyme reaction was pH 4.5 to 5.0 at 55°C. The purified enzyme was stable at 55°C or below and in buffer at pH 3 to 8. The activity was inhibited by mercury, silver, and copper ions. The kinetics of this enzyme, with p-nitrophenyl-α-d-galactoside as substrate, was determined: K(m) was about 0.8 mM, and V(max) was 39 μmol/min per mg of protein. Enzymatic hydrolysis of melibiose, raffinose, and stachyose was analyzed by thin-layer chromatography.